Deformation-resembling microstructure created by fluid-mediated dissolution–precipitation reactions - Liene Spruzeniece; Sandra Piazolo; Helen E. Maynard-Casely (Nature Communications, 2017)
Microstructural features of deformed rocks are used to reveal deformation stresses and temperatures. Here, the authors conduct experiments showing that misleading microstructures form during fluid-mediated mineral reactions under static conditions, and propose new criteria for microstructure identification.